2010
DOI: 10.4103/0378-6323.58677
|View full text |Cite
|
Sign up to set email alerts
|

Clinico-allergological pattern of allergic contact dermatitis among 70 Indian children

Abstract: This study reflects the current status of childhood ACD of this region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 26 publications
1
33
2
Order By: Relevance
“…Sample size ranged from 45 to 6708 subjects. Thirty‐nine studies were performed in Europe, six in North America, and five in South America or Asia . There was some overlap of subjects between some of the series (17 and 22, 18 and 24, 26 and 32, 6 and 48, 16 and 21, 41, 47 and 57).…”
Section: Discussionmentioning
confidence: 99%
“…Sample size ranged from 45 to 6708 subjects. Thirty‐nine studies were performed in Europe, six in North America, and five in South America or Asia . There was some overlap of subjects between some of the series (17 and 22, 18 and 24, 26 and 32, 6 and 48, 16 and 21, 41, 47 and 57).…”
Section: Discussionmentioning
confidence: 99%
“…Others found no difference in sensitization rates between different age groups (4, 19, 23, 28, 29). Hammonds et al (23), however, noted a trend for a higher rate among boys aged 3–10 years, which decreased with age, but suggested that this finding could be attributable to the small numbers in the specific age groups (8 patients were male, and 6 of these had positive patch test reactions).…”
Section: Age and Contact Sensitizationmentioning
confidence: 96%
“…Understanding the allergic cascade and the resulting release of inflammatory mediators supports the use of certain classes of medications-specifically mastcell stabilizers, leukotriene inhibitors, steroids, and/ or antihistamines-for any allergic reaction regardless of its severity. Sarma and Ghosh (2010) reported that children might be exposed to chemicals in developing countries where controls for product safety guidelines are more relaxed. These investigators reported that 18 of the 70 children tested (25.7%) were atopic and that the most common allergens were parabens (43%), potassium dichromate (27%), and fragrance mix (26%).…”
Section: Allergic Contact Dermatitismentioning
confidence: 98%